Study guides

☆☆

Q: X squared minus 2x minus 3 divided by x minus 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The question contains an expression but not an equation. You cannot solve an expression.

Numerator = (x + 4)*(x + 3) Denominator = (2x - 1)*(x + 3) Calcelling out the common factor, (x + 3), the answer is (x + 4) divided by (2x - 1) provided x â‰ 0.5

(4+x) (2x-3)

(2x-3)(x-1)

After long division, (2x2-5x+5)/(x-2) = 2x-1+3/(x-2).

Related questions

2x squared minus 5x minus 3 factored is (2x+1)(x-3).

2x squared - 5x - 3 = (2x +1)(x -3)

(x - 2)(2x + 3)

The question contains an expression but not an equation. You cannot solve an expression.

Numerator = (x + 4)*(x + 3) Denominator = (2x - 1)*(x + 3) Calcelling out the common factor, (x + 3), the answer is (x + 4) divided by (2x - 1) provided x â‰ 0.5

(4+x) (2x-3)

4x2 - 9 = (2x + 3)(2x - 3)

(2x-3)(x-1)

After long division, (2x2-5x+5)/(x-2) = 2x-1+3/(x-2).

(2x - 1)(x + 3)

(2x - 3)(x + 2)

(2x - 3)(x + 2)

People also asked